Diseño de estrategias mercadológicas de promoción digital para difusión de la música pop nacional a millennials guayaquileños - Guzmán Barquet, Eduardo Andrés (2020)
The present work provides information about the scarce diffusion that Ecuadorian pop music has had at the local level, causing the national industry of the sector to be affected by the scarce approval of the songwriters of the genre by the millennials in the city of Guayaquil. The design of digital promotion strategies, aims to spread the national pop genre, in a way that allows the recognition of singers of this genre in an environment updated to new trends. For the development of this research, theoretical bases were used to contextualize what is related to music and its expansion through marketing strategies. This research used a semi-structured interview and a questionnaire of closed questions for the collection of primary information to the target group. Through the calculation of the size of the sample, 387 surveys were conducted. Among the most relevant results highlighted in this research are: (a) YouTube® is the platform most used by these young people; and (b) they prefer the artist to be a male soloist. Finally, a proposal was developed for the incentive of national pop music to millennials of the city of Guayaquil.